Komunikasi Hiperpersonal Avoskin dalam Memitigasi Isu Pencemaran Lingkungan Melalui Instagram - Riansa Putra Fajri; Arya Wirawan Maulana (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
The rapid growth of the skincare industry in Indonesia presents a paradox: increasing environmental pollution caused by the use of single-use packaging. This study examines how Avoskin utilizes hyperpersonal communication through its Instagram account, @avoskinbeauty, to mitigate environmental issues. The aim of this research is to explore the application of hyperpersonal communication elements—selective self-presentation, idealized receiver perception, channel management, and feedback loop—in Avoskin’s sustainability messaging. This study employs a qualitative approach using a descriptive-analytical method and Systematic Documentary Review (SDR). The content analyzed was published between January 1 and April 30, 2025. Findings indicate that Avoskin consistently promotes sustainability values through educational digital content. These efforts not only inform the audience but also foster emotional resonance and active participation through likes, comments, and direct involvement in recycling programs. The study concludes that hyperpersonal communication via social media serves as an effective platform to strengthen a company’s green identity and raise public ecological awareness. Avoskin exemplifies how digital communication can strategically integrate commercial interests with environmental responsibility.